Influence and Effects of Novel Nanorod Structured Polypyrrole-Nickel(II) Oxide Nanocomposites - Dhachanamoorthi1, N.; Nishara Begum2, A. (Asian Journal of Chemistry, 2013)
Polypyrrole-nickel(II) oxide (PPy-NiO) nanocomposites have been synthesized for the first time through an in situ chemical polymerization of pyrrole in the presence of NiO nanoparticles of less than 50 nm. The organic-inorganic hybrid nanocomposite materials PPy-NiO with different NiO (25, 50 and 100 %) in wt. % were prepared by mechanical mixing method. The monomer (pyrrole) was used as an oxidizing agent (ammonium peroxydisulfate) and added dodecylbenzene sulfonic acid (DBSNa) as a dopant and the mixture was continuously stirring well and maintained at 0-5 ºC, after synthesized, the nanoparticle nickel oxide powder was added. The FTIR results, reveals the presence of the vibration bands of a dopant ion and other characterization bands, which confirm the prepared samples were polymer nanocomposite samples. Further, characterization studies such as, UV-VIS spectroscopy, X-ray diffraction (XRD) and scanning electron microscopy (SEM) also reveals the presence of nanocomposite. An analytical technique for the elemental analysis characterization was analyzed by the use of energy dispersive X-ray analysis spectroscopy (EDAX).